The blood-brain barrier - Lessons from moody flies. - Daneman, R.; Barres, B.A. (Cell, 2005)
Despite the importance of the blood-brain barrier (BBB), little is known about the molecular mechanisms that control its integrity. The identification of moody, a gene required for the formation and maintenance of the Drosophila BBB, provides new insight into how paracellular junctions are formed at the barrier. Meanwhile, moody also has been identified in a screen for fly mutants with altered sensitivity to cocaine, remarkably implicating the BBB in the physiological response to narcotics.